2022
DOI: 10.1002/mrm.29149
|View full text |Cite
|
Sign up to set email alerts
|

On the fat saturation effect in quantitative ultrashort TE MR imaging

Abstract: Purpose: To investigate the effect of fat saturation (FatSat) on quantitative UTE imaging of variable knee tissues on a 3T scanner.Methods: Three quantitative UTE imaging techniques, including the UTE multiecho sequence for T * 2 measurement, the adiabatic T 1ρ prepared UTE sequence for T 1ρ measurement, and the magnetization transfer (MT)-prepared UTE sequence for MT ratio (MTR) and macromolecular proton fraction (MMF) measurements were used in this study. Twelve samples of cartilage and twelve samples of men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A range of MMF values in muscles has been reported in the literature. In human lower extremity muscles, values generally range from 6% to 9%, 14,18,40 whereas values between 12% and 17% have been reported in pigs and cattle. 15,41 Thus, the MMF values we obtained in the rat rotator cuff muscles are within the expected range, although are probably underestimated in the injured shoulders due to residual edema.…”
Section: Discussionmentioning
confidence: 98%
“…A range of MMF values in muscles has been reported in the literature. In human lower extremity muscles, values generally range from 6% to 9%, 14,18,40 whereas values between 12% and 17% have been reported in pigs and cattle. 15,41 Thus, the MMF values we obtained in the rat rotator cuff muscles are within the expected range, although are probably underestimated in the injured shoulders due to residual edema.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, a conventional fat-saturation module was employed to suppress fat. Chen et al [41] demonstrated that these conventional fat saturation modules could decrease T1ρ in short T2 tissues, such as the quadriceps tendon, by approximately 9%. This reduction could be attributed to the broad frequency spectrum of these tissues, which might be in proximity to or overlapping with the signal peaks from fat.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al. investigated the effects of fat saturation on three quantitative UTE images including , T 1ρ , and MT ( 59 ). These sequences were implemented with and without fat saturation on knee cartilage samples and whole cadaveric knee specimens at 3T.…”
Section: Ute With Fat Suppressionmentioning
confidence: 99%